2017
DOI: 10.1038/s41598-017-07525-w
|View full text |Cite
|
Sign up to set email alerts
|

Red (660 nm) or near-infrared (810 nm) photobiomodulation stimulates, while blue (415 nm), green (540 nm) light inhibits proliferation in human adipose-derived stem cells

Abstract: We previously showed that blue (415 nm) and green (540 nm) wavelengths were more effective in stimulating osteoblast differentiation of human adipose-derived stem cells (hASC), compared to red (660 nm) and near-infrared (NIR, 810 nm). Intracellular calcium was higher after blue/green, and could be inhibited by the ion channel blocker, capsazepine. In the present study we asked what was the effect of these four wavelengths on proliferation of the hASC? When cultured in proliferation medium there was a clear dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
110
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 47 publications
(52 reference statements)
10
110
2
1
Order By: Relevance
“…Therefore, the observation of photorejuvenation, wound healing or hair regrowth effects cannot yet be associated with a stimulation/inhibition of a particular cell type, for example, dermal fibroblasts. Some of our results concurred with previous research studies . In particular, it was clear that three consecutive exposures to short visible wavelengths (⇐530 nm), exerted inhibitory effects on DFs while long visible and NIR wavelengths (>=530 nm) had a neutral impact at standard environmental oxygen concentration.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the observation of photorejuvenation, wound healing or hair regrowth effects cannot yet be associated with a stimulation/inhibition of a particular cell type, for example, dermal fibroblasts. Some of our results concurred with previous research studies . In particular, it was clear that three consecutive exposures to short visible wavelengths (⇐530 nm), exerted inhibitory effects on DFs while long visible and NIR wavelengths (>=530 nm) had a neutral impact at standard environmental oxygen concentration.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study also agrees with previously published data on the involvement of ROS as part of the immediate effect of light on cells [16,18,[21][22][23][24]50]. It has been demonstrated that exposure to short visible wavelength light induced ROS in various models [22,50] and could result in DNA damage in human epithelial cells for example [22].…”
Section: Cluster (High Dose)supporting
confidence: 92%
See 2 more Smart Citations
“…The most important alternative chromophore appears to be transient receptor potential (TRP) ion channels that can be activated by light or heat . An example is TRPV1 that can be activated by blue or green light and by longer wavelength NIR light (980 nm) that targets water in the form of nanostructured exclusion zone water clusters . Regardless of whether CCO is activated by red/NIR light, or TRP ion channels are activated by blue/green/980 nm light, the cellular results have some aspects in common, but also display some differences.…”
Section: Introductionmentioning
confidence: 99%